2022
DOI: 10.1016/j.clnu.2021.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Feeding intolerance in critically ill patients with COVID-19

Abstract: Background and Aims Early reports suggest significant difficulty with enteral feeding in critically ill COVID-19 patients. This study aimed to characterize the prevalence, clinical manifestations, and outcomes of feeding intolerance in critically ill patients with COVID-19. Methods We examined 323 adult patients with COVID-19 admitted to the intensive care units (ICUs) of Massachusetts General Hospital between March 11-June 28, 2020 who received enteral nutrition. Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 39 publications
0
33
0
2
Order By: Relevance
“…In fact, the amount of proteins administered with the nutritional support was significantly lower in non-survivors (see figure 2 ). One possible explanation for such a reduced protein administration might be a higher incidence of intolerance to enteral feeding in non-survivors, which is known to be a marker of a more severe disease state and associated with a worse outcome, especially in the COVID-19 population [62] . No differences were found in the cumulative energy (calorie) deficit, likely because a significant part of the calorie provision came from intravenous lipids from propofol infusion.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the amount of proteins administered with the nutritional support was significantly lower in non-survivors (see figure 2 ). One possible explanation for such a reduced protein administration might be a higher incidence of intolerance to enteral feeding in non-survivors, which is known to be a marker of a more severe disease state and associated with a worse outcome, especially in the COVID-19 population [62] . No differences were found in the cumulative energy (calorie) deficit, likely because a significant part of the calorie provision came from intravenous lipids from propofol infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors could explain malnutrition during this acute phase, including marked systemic inflammation driving hypermetabolism and muscle catabolism, and prolonged periods of bedrest driving disuse atrophy. Up to 40% of patients with COVID-19 experience gastrointestinal symptoms ranging from nausea, vomiting, anorexia, diarrhea and abdominal distention, especially in ICU COVID patients [4], which can further deter eating and impact the tolerance of nutritional support [5]. Olfactory and gustatory dysfunction [6] may also contribute to weight loss [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Medical teams have become increasingly aware of the importance of multidisciplinary care, taking into account fatigue and functional disability, but nevertheless overlooking the nutritional aspect and the importance of the decrease in muscle strength [1]. Nowadays, muscle weakness and fatigue appear as a frequent complaint among these patients [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies so far have provided limited data about nutrition support. A USA cohort [ 24 ] revealed that more than half of the participants (56%) presented intolerance to enteral nutrition, which was associated with higher ICU stay and in-hospital mortality, whereas a similar study among intubated patients from Mexico revealed a lower prevalence of intolerance to enteral nutrition—about 32% [ 25 ]. A series of 176 critically ill patients with COVID-19 disease [ 26 ] managed to reach their energy and protein requirements during the first week of admission especially through the use of supplemental parenteral nutrition.…”
Section: Discussionmentioning
confidence: 99%